Environmental technology, economic complexity, renewable electricity, environmental taxes and CO2 emissions: Implications for low-carbon future in G-10 bloc - Saqib, Najia; Radulescu, Magdalena; Usman, Muhammad; Balsalobre-Lorente, Daniel; Cilan, Teodor (Heliyon, 2023)
This study investigates the impact of environmental technological innovation, economic complexity, energy productivity, the use of renewable electricity generation, and environmental taxes on carbon dioxide (CO2) emissions in the G-10 countries for the timeframe from 1995 to 2020. The purpose of the study is to examine the need for a clear plan or strategy to achieve environmental objectives in G-10 countries. In both short-term and long-term projections, the increased use of environment-based technology, economic complexity, and renewable electricity generation has a major positive impact on carbon emission reduction. Moreover, the results demonstrate both unidirectional and bidirectional causality from carbon emissions to renewable energy, electrical generation, and environment-based technologies, respectively. Based on the results, the study proposes a number of concrete policies, such as updating modernized tax systems, increasing tax collection, providing individuals with the means to finance the Sustainable Development Goals through incentive regulations, and making grants from international organizations and the private sector available to finance investments toward the Sustainable Development Goals (SDGs) and carbon neutrality environment targets. This is the study's most significant contribution in order to attain a sustainable and low-carbon future in the G-10 countries, which has policy implications for governments and policymakers.
Keywords: Environmental taxes; G-10 countries; Economic complexity; SDGs; Energy productivity; Renewable electricity